The Effect of Molten Salt Composition on Carbon Structure: Preparation of High Value-Added Nano-Carbon Materials by Electrolysis of Carbon Dioxide - Yi Cheng; Liangxing Li; Lirong Xue; Jiahang Wu; Jingsong Wang; Xilin Huang; Chunfa Liao (Nanomaterials)
The electrochemical conversion of CO2 into high value-added carbon materials by molten salt electrolysis offers a promising solution for reducing carbon dioxide emissions. This study focuses on investigating the influence of molten salt composition on the structure of CO2 direct electroreduction carbon products in chloride molten salt systems. Using CaO as a CO2 absorber, the adsorption principle of CO2 in LiCl-CaCl2, LiCl-CaCl2-NaCl and LiCl-CaCl2-KCl molten salts was discussed, and the reasons for the different morphologies and structures of carbon products were analyzed, and it was found that the electrolytic efficiency of the whole process exceeded 85%. Furthermore, cathode products are analyzed through Scanning Electron Microscope (SEM), X-Ray Diffractometer (XRD), Thermal Gravimetric Analyzer (TGA), Raman Spectra and Fourier Transform Infrared (FTIR) techniques with a focus on the content and morphology of carbon elements. It was observed that the carbon content in the carbon powder produced by molten salt electrochemical method exceeded 99%, with most carbon products obtained from electrolysis in the Li-Ca chloride molten salt system being in the form of carbon nanotubes. In contrast, the Li-Ca-K chloride system yielded carbon nanospheres, while a mixture was found in the Li-Ca-Na chloride system. Therefore, experimental results demonstrate that altering the composition of the system allows for obtaining the desired product size and morphology. This research presents a pathway to convert atmospheric CO2 into high value-added carbon products.